2008
DOI: 10.4028/www.scientific.net/kem.373-374.69
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Substrate Temperature on Microcracks Formation in Plasma-Sprayed Yttria-Stabilized Zirconia Splats

Abstract: YSZ molten droplets created by plasma spraying were deposited on the YSZ substrate preheated to different temperature from 75oC to 1000oC. The results showed that there is little change in crack spacing when substrate temperature is less than about 740oC, and a significant increase in crack spacing from 3.54 μm at 740oC to 10.91 μm at 1000oC was observed. A simple qualitative model was proposed on the basis of the origin of thermal stresses to explain the influence of substrate initial temperature on crack den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…However, although based on those results reported it could be considered that the coating consisting of wellbonded lamellae can be deposited when droplets are projected on a substrate surface at certain high temperature, few investigations were involved in the effect of coating surface temperature or substrate temperature on the lamellar bonding formation. Recently, it was evidently revealed using YSZ deposits that through the control of substrate temperature, the bonding ratio and subsequently the coating properties can be significantly changed ( Ref 17,30). During deposition, the substrate temperature, especially the coating surface temperature prior to droplet impact can be considered to be a key factor, which influences the deposition characteristic of the molten droplets and bonding of the splat to the prior deposited coating, and subsequently influences the properties of deposited coating.…”
Section: Introductionmentioning
confidence: 99%
“…However, although based on those results reported it could be considered that the coating consisting of wellbonded lamellae can be deposited when droplets are projected on a substrate surface at certain high temperature, few investigations were involved in the effect of coating surface temperature or substrate temperature on the lamellar bonding formation. Recently, it was evidently revealed using YSZ deposits that through the control of substrate temperature, the bonding ratio and subsequently the coating properties can be significantly changed ( Ref 17,30). During deposition, the substrate temperature, especially the coating surface temperature prior to droplet impact can be considered to be a key factor, which influences the deposition characteristic of the molten droplets and bonding of the splat to the prior deposited coating, and subsequently influences the properties of deposited coating.…”
Section: Introductionmentioning
confidence: 99%
“…Those results are well consistent with that reported in previous studies. [22][23][24] According to splashing model proposed by Li et al, 23 the splashing is attributed to the evaporated gas resulting from adsorbates on the substrate surface. At a high preheating temperature range within which disk shaped splats are observed the adsorbates on the substrate surface will be completely removed and accordingly the bonding formation between splat and the substrate becomes possible.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have shown that flattened particles have connected vertical cracks (Ref 4,41,42,47,(51)(52)(53). Crack width decreases with increasing substrate temperature.…”
Section: Deposition Behavior Of Small Molten Particlesmentioning
confidence: 98%
“…It is beneficial to form dense coatings, and consequently, to improve the gastight ability. Li et al (Ref 27,51) have reported that, when ceramic particles are deposited by using conventional plasma spraying, deposition temperature significantly affects the interface bond between flattened particles and the substrate. However, in this work, small size flattened particles can bond well with the Fig.…”
Section: Deposition Behavior Of Small Molten Particlesmentioning
confidence: 99%